ANTHROPOLOGICAL ASPECTS OF INTERNET COMMUNICATIONS - Іщук, Н. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2014)
This article examines the anthropological environment of the Internet in the context of discourses plurality of the personal self-realization in the Web. The specific character and the most important characteristics of a virtual personality in its interaction with the spiritual world of the medium have been revealed.